Природа і людина в середньому й верхньому плейстоцені України: основні тренди заселення та культурної динаміки - Степанчук, В.М.; Сапожников, І.В. (Кам’яна доба України, 2010)
У статті на основі залучення широкого кола природничих і археологічних даних
розглядаються найбільш загальні закономірності початкового заселення, наступного освоєння та загальної динаміки культурно-історичного розвитку на території сучасної України протягом середнього і верхнього плейстоцену. Paper deals with the most important regularities and shifts of cultural development and patterns of peopling and colonization of the territory of modern Ukraine in course of Middle and Upper Pleistocene. Evidence of Palaeolithic occupations currently is dated to OIS 13, 11, 7 - 2. For the first of these periods presence of population is reported for Ukrainian Transcarpathia, west of Carpathian arc. First reliable evidence of human presence at the terrains east of Carpathian arc is dated to OIS 11. Since OIS 7 till the very end of the Pleistocene, territory of Ukraine demonstrates repetitive affluxes and refluxes of population. Since OIS 5e pattern of peopling is characterized by presence of permanently peopled core areas in extreme south and west of the country, where the most rich and predictable biological and mineral resources were concentrated in zone of mosaic landscapes of low mountains and elevations. Starting from somewhere ca. 32 ky BP the process of gradual colonization of open landscapes was begun. Essential shift had occurred between 22-20 ky BP, when population for the first time was concentrated in zone of open steppe. Strategy of colonization of the territory abruptly changed after 18 ky BP; since this moment territory of Ukraine was everywhere occupied permanently, stable, and continuously.